Prototype Innovation of Online Tire Patching Application (BalBan) As an Effort to Learn from Experience: Case Study of Bantul Regency and its surroundings - Putra, Riza Dian Ade; Abhirama, Muhammad Erga; wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2023)
When a tire is damaged, vehicle owners need to repair it immediately to maintain the safety and performance of their vehicle. Traditionally, people have to go to a repair shop or physical tire shop to repair damaged tires. However, in reality not all incidents of punctured tires are in accordance with the plans that are already available, there are many moments that inevitably make us have to walk far to find the existence of a conventional tire patch service. We took the initiative to create a prototype of an online tire patch service, namely BalBan. BalBan is an online tire patch service enabling vehicle owners to order tire patch services online through a mobile application or website. The system development method used in this study is the prototype method. To achieve success, Online tire patching applications need to focus on their strengths, such as developing a good user experience, strong partnerships with repair shops and mechanics, and building user trust through positive ratings and reviews. It is also important to continuously monitor market trends and adapt to changes in the tire patch service industry.